2017
DOI: 10.1186/s12891-017-1692-0
|View full text |Cite
|
Sign up to set email alerts
|

Acromioclavicular joint dislocation treated with Bosworth screw and additional K-wiring: results after 7.8 years – still an adequate procedure?

Abstract: BackgroundThe acromioclavicular (AC) joint dislocation is a major reason for shoulder instability. Different concepts of treatment and surgical methods are described in the literature. Thus, the purpose of this study was to present our data of long-term follow-up of patients having undergone treatment of acromioclavicular (AC) joint dislocation using the Bosworth Screw with additional K-wiring.MethodsThis study was conducted as a retrospective single centre data analysis. All patients treated operatively for A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…While Bosworth screws are no longer used in isolation, they are still sometimes combined with other treatment modalities. Tiefenboeck et al [ 23 ] showed that Bosworth screw fixation with additional K-wire stabilization offers good-to-excellent functional outcomes and was well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…While Bosworth screws are no longer used in isolation, they are still sometimes combined with other treatment modalities. Tiefenboeck et al [ 23 ] showed that Bosworth screw fixation with additional K-wire stabilization offers good-to-excellent functional outcomes and was well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…performed biomechanical tests, which demonstrated the superiority of an anatomic CC ligament reconstruction over the modified Weaver-Dunn technique. Numerous modifications of the Weaver-Dunn technique and anatomic CC reconstruction have been reported including both open and arthroscopic options 7, 8, 9, 12, 13. Despite these efforts, up to 80% of patients following AC reconstruction have been reported to lose radiographic reduction, and between 20% and 30% of patients treated surgically are reported to have complications leading to reoperation 14, 15.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous modifications of the Weaver-Dunn technique and anatomic CC reconstruction have been reported including both open and arthroscopic options. 7 , 8 , 9 , 12 , 13 Despite these efforts, up to 80% of patients following AC reconstruction have been reported to lose radiographic reduction, and between 20% and 30% of patients treated surgically are reported to have complications leading to reoperation. 14 , 15 The goal of the presented technique is to use the biomechanical data available to create a construct that minimizes failure and provides anatomic restoration of the AC joint using a reinforced biologic construct.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations